SIFAT FISIKO KIMIA BERAS MERAH GOGO LOKAL ENDE [The Physico-chemical Properties of Local Ende High Land Brown Rice] - Herianus J.D. Lalel; Zainal Abidin; Lewi Jutomo (Jurnal Teknologi dan Industri Pangan, 2009)
Ten strains of Ende high land brown rice were assessed to underpin their physico-chemical properties related to their potential uses.  Are Ndota has bigger grain size and smoother gel consistency than others (63.50 mm gel length). It potentially can be used as food thickeners and baby foods.  Are Kea showed the highest water imbibition ability (90.99%), the fastest wettability (12.11 sec), and the highest dispersibility value (2,50 %) due to its high amylose content (33.21 %). Potentially, Are kea can be used for noodles. The variety also had small repose angle (27.46°), therefore it can be easily transported.